Apontamentos sobre bibliotecas em escolas do campo no estado do Paraná - Gehrke, Marcos; Bufrem, Leilah Santiago [UNESP] (Univ Fed Paraiba Ccsa, 2013)
This paper presents the partial results of an investigation about school libraries in countryside schools of the public educational system in the state of Paraná. The work is based on reflections about the literature related to the theme and the analysis of this reality. It aims at characterizing the subjects of the countryside school, the physical space, materials and common practices at the school libraries. The work describes the influence of the aspects aforementioned on the existence, planning and development of activities, also describing their contribution to the formation process of school subjects. The investigation also performs a descriptive field research, employing direct observation and the application of a survey in 425 countryside schools, considering a total number of 2120 schools in the Paraná school system. The survey obtained a return rate of 83% from representatives of public countryside schools in Paraná. The results indicated that the schools need a project for reading and writing, in which the library would be engaged. The paper argues that state and the university should contribute to the formation of the professionals of the institution and that the school library should be open to the community, acting both as a service provider and a stimulator of writing and reading practices. The investigation concludes that it is necessary to 'occupy the libraries of the countryside schools', understanding them not only as a communication spot, but also as a place for knowledge production. Furthermore, the authors suggest the library materials should be produced locally and that the state should turn this practice into a public policy.
Notes about libraries in countryside schools in the state of Paraná
Keywords: Countryside education; School libraries; Reading; Writing; Parana